2021
DOI: 10.1007/s00429-021-02351-3
|View full text |Cite
|
Sign up to set email alerts
|

Human primary visual cortex shows larger population receptive fields for binocular disparity-defined stimuli

Abstract: The visual perception of 3D depth is underpinned by the brain’s ability to combine signals from the left and right eyes to produce a neural representation of binocular disparity for perception and behaviour. Electrophysiological studies of binocular disparity over the past 2 decades have investigated the computational role of neurons in area V1 for binocular combination, while more recent neuroimaging investigations have focused on identifying specific roles for different extrastriate visual areas in depth per… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 76 publications
(133 reference statements)
0
5
0
Order By: Relevance
“…When a disparity-defined stimulus is used for mapping the visual areas compared to a flickering checkerboard, the pRF sizes are larger for the disparity-defined stimulus by an amount predicted by computational models of binocular combination. All adapted from Alvarez et al (2021). of depth. Neurophysiological studies have indicated that neurons in primary visual cortex respond to the false matches in aRDS patterns (Cumming & Parker, 1997) but the response to these patterns is significantly reduced higher within the ventral visual stream, notably in V4 and IT (Janssen et al, 2003;Tanabe et al, 2004).…”
Section: Use Of Functional Mri To Understand Human Binocular Vision E...mentioning
confidence: 99%
See 2 more Smart Citations
“…When a disparity-defined stimulus is used for mapping the visual areas compared to a flickering checkerboard, the pRF sizes are larger for the disparity-defined stimulus by an amount predicted by computational models of binocular combination. All adapted from Alvarez et al (2021). of depth. Neurophysiological studies have indicated that neurons in primary visual cortex respond to the false matches in aRDS patterns (Cumming & Parker, 1997) but the response to these patterns is significantly reduced higher within the ventral visual stream, notably in V4 and IT (Janssen et al, 2003;Tanabe et al, 2004).…”
Section: Use Of Functional Mri To Understand Human Binocular Vision E...mentioning
confidence: 99%
“…When a disparity-defined stimulus is used for mapping the visual areas compared to a flickering checkerboard, the pRF sizes are larger for the disparity-defined stimulus by an amount predicted by computational models of binocular combination. All adapted from Alvarez et al (2021).…”
Section: Brief Primer To Magnetic Resonance Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Three other papers explore the functional properties of V1 and how they change according to different conditions. Alvarez et al (2021) report that human V1 shows larger population receptive fields (pRF; Dumoulin and Wandell 2008) for disparity-defined stimuli, compared with other types of stimuli, and that this observation can be explained based on the binocular energy model (Ohzawa et al 1990). Further, Silva et al (2021) report that pRF estimates are affected by aging, revealing correlations between visual acuity, retinal thickness, and cortical visual area size in human participants.…”
mentioning
confidence: 93%
“…In general, there is a certain difference in the image position of the corresponding features presented to the retina of both eyes due to the horizontal distance between the eyes, called binocular disparity (Angelis et al, 1995;Gonzalez and Perez, 1998;Alvarez et al, 2021). If the corresponding image point can be found on both retinas, this disparity in position can be retrieved, and the relative depth of the object can be measured (Tsirlin et al, 2014;Verhoef et al, 2016;Chen et al, 2021;Vishwanath, 2021).…”
Section: Introductionmentioning
confidence: 99%